2007
DOI: 10.7326/0003-4819-147-6-200709180-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Training, Resistance Training, or Both on Glycemic Control in Type 2 Diabetes

Abstract: Either aerobic or resistance training alone improves glycemic control in type 2 diabetes, but the improvements are greatest with combined aerobic and resistance training. ClinicalTrials.gov registration number: NCT00195884.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
867
16
47

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,049 publications
(1,039 citation statements)
references
References 20 publications
55
867
16
47
Order By: Relevance
“…The key finding in the present randomized controlled trial was no reductions in resting SBP or DBP were achieved among exercisers at 6 months despite a training effect as evidenced by increased fitness, improved glycemic control and improved body composition. Thus, our study provides a higher level of evidence, and corroborates the finding of a recent trial, 14 supporting the conclusion of ACSM/ADA Abbreviations: SE standard error *Test for difference on change from baseline **Test for between-group difference on the change from baseline regarding lack of efficacy of exercise for reducing BP in this population. Several factors might explain the lack of change in BP.…”
Section: Discussionsupporting
confidence: 89%
“…The key finding in the present randomized controlled trial was no reductions in resting SBP or DBP were achieved among exercisers at 6 months despite a training effect as evidenced by increased fitness, improved glycemic control and improved body composition. Thus, our study provides a higher level of evidence, and corroborates the finding of a recent trial, 14 supporting the conclusion of ACSM/ADA Abbreviations: SE standard error *Test for difference on change from baseline **Test for between-group difference on the change from baseline regarding lack of efficacy of exercise for reducing BP in this population. Several factors might explain the lack of change in BP.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, 59/218 (27%) of participants included in this analysis sustained an adverse event during the course of the study, including 16 participants in the combined exercise group, 19 participants in the resistance exercise group, 16 participants in the aerobic exercise group, and eight participants in the control group. The main outcomes of the trial have been reported previously [8]. Briefly, the absolute change in the HbA 1c value in combined compared with control groups was −0.96 percentage points (95% CI −1.32, −0.61).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance exercise training caused some clinically important improvements in physical health status; however, none of the exercise training programmes enhanced the mental component of health status relative to non-exercise control. While aerobic and resistance exercise training and a combination of both unmistakably improve glycaemic control [2,8], effects on patient-reported quality of life outcomes during a 6-month exercise intervention are less clear. Duality of interest The authors declare that there is no duality of interest associated with this manuscript.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations